COMPARATIVE STUDY OF WOMEN STEREOTYPES IN BJÖRN RUNGE`S FILM THE WIFE AND GARY ROSS` FILM OCEAN`S 8 - Johanna Meidyta Charissa; Dian Eka Sari (STBA Prayoga Padang, 2022)
Abstract . This article aims to compare women stereotypes, in two different films by analyzing the different ways between two different generations facing womenstereotypes. Socialist feminist theory by Mary Ellmann that women stereotypes are used in this article by applying several concepts: confinement, compliance, and piety. The writer uses a descriptive qualitative method to explain the data. There are two findings, the first finding is the silent generation applies women stereotypes while generation X does not apply women stereotypes. The second finding is silent generation is influenced by social perspective while generation X does not influence by social perspective.